ESTIMASI CADANGAN KLAIM PADA ASURANSI UMUM DENGAN METODE CHAIN LADDER - PERTIWI, SUNDANIS AGUNG; WIDANA, I NYOMAN; SARI, KARTIKA (E-Jurnal Matematika, 2023)
Based on the 2020 Insurance Statistic Data released by OJK, the ratio of gross claims to gross premiums has increased due to the growth of gross premiums followed by increasing claims paid. Thus, the insurance company is obliged to provides claim reserve that is important to be estimated appropriately, especially outstanding claim reserves. This is because outstanding claim reserves are needed to cover underpayment on future claims. One popular method to estimate outstanding claim reserves is the Chain Ladder method. This study aims to determine the results of the estimated outstanding claim reserves on general insurance using Mack’s CL method. CL method is a method to estimate claim reserves simply without satisfying certain distribution assumptions. This study uses incremental run-off triangle data taken from Weindofer's research article (2012) with an event period of 2005-2012 and a development period of 8 years. Based on the calculations in this study, an estimated outstanding claim reserve of USD 20,109.82 was obtained, meaning the funds that must be prepared amounted to USD 20,109.82 in 2013 by the general insurance company that owns the data studied. It also serves as a benchmark in the determination of claim reserves in the 2013 financial statements